An Investigation of the themes of Soheil Mahmoudi's short poems on the Basis of Haiku and Senryu in his three books: The Dream of Tree is Deep-rooted, Spring is the Train of Your Dress, and Now We Are Both Alone - raziye fooladisepehr (مجله مطالعات ایرانی, 2018)
Abstract Short poems deliver the most meaning in the shortest time to today’s thoughtful and serious audience, and because of being free from language, time, and meter constraints, is a kind of incaution, freedom, and self-assertion against conservative forms and ideas. Although short poem is among our original literary heritages, sometime it is also comparable to the two Japanese forms of haiku and senryu. It can be said that the reason for the increasing attention to this kind of poetry is its synchronization and harmony with the pace of modern society. While being adherent to the structure of haiku and senryu, the short poems in the three studied books have gone further in terms of theme and content, and being based on improvised poetry, they are individuated and free from the shackles of repetition and imitation. The content of his poems reveal traces of national, ritual culture and other properties of the time and the society in which the poet lived in his poem’s them.